New mesozoic and cenozoic fossils from Ecuador: invertebrates, vertebrates, plants, and microfossils (2018)
Ecuador is well known for its extensive extant biodiversity, however, its paleobiodiversity is still poorly explored. Here we report seven new Mesozoic and Cenozoic fossil localities from the Pacific coast, inter-Andean depression and Napo basin of Ecuador, including vertebrates, invertebrates, plants, and microfossils. The first of these localities is called El Refugio, located near the small town of Chota, Imbabura Province, from where we report several morphotypes of fossil leaves and a mycetopodid freshwater mussel of the Upper Miocene Chota Formation. A second site is also located near the town of Chota, corresponding to potentially Pleistocene to Holocene lake deposits from which we report the occurrence of leaves and fossil diatoms. A third locality is at the Pacific coast of the country, near Rocafuerte, a town in Esmeraldas Province, from which we report a late Miocene palm leaf. We also report the first partially articulated skull with teeth from a Miocene scombridid (Mackerels) fish from El Cruce locality, and completely preserved seeds from La Pila locality, both sites from Manabí Province. Two late Cretaceous fossil sites from the Napo Province, one near Puerto Napo showing a good record of fossil shrimps and a second near the town of Loreto shows the occurrence of granular amber and small gymnosperms seeds and cuticles. All these new sites and fossils show the high potential of the sedimentary sequences and basins of Ecuador for paleontological studies and for a better understanding of the fossil record of the country and northern South America.